Pengaruh Model PAKEM terhadap Keterampilan Proses Sains Anak Kelompok B di TK Negeri Desa Tukadmungga - Ni Putu Lia Suarningsih; I Ketut Gading; Dewa Ayu Puteri Handayani (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
Science process skills include observing, classifying, comparing, measuring, communicating, and experimenting. Not all students can master science process skills well, so it is necessary to apply appropriate learning methods to improve students' science process skills. This study aimed to determine the PAKEM learning model's effect on group B children's science process skills. The type of research carried out was a quasi-experimental study with a pretest-posttest control group design. The population in this study is 80 people. The sample in this study, the experimental group, consisted of 25 people, while the control group consisted of 28 people. Data on the results of science process skills were collected using an instrument in the form of an observation sheet. It was analyzed using descriptive and inferential statistical analysis techniques (t-test). The descriptive analysis results obtained that the experimental group's average score was greater than the average score of the control group. Based on the results of the data analysis, it can be concluded that there is a significant influence of the PAKEM learning model on the science process skills of group B children.